Productivity and Catch Composition of Purse Seine Fisheries at The Kasiwa Fish Landing Base, Mamuju Regency, West Sulawesi - Nurliana; Femiliani Novitasari; Widya Utami; Hardianty Nur (Hasanuddin University, 2025)
This study aims to analyze the productivity and catch composition of fish using purse seine gear at the Fish Landing Base (PPI) Kasiwa, Mamuju Regency, West Sulawesi. The research employed a quantitative approach, with primary data collected from two purse seine vessels during one month of fishing operations. Secondary data were obtained from relevant literature and institutions. The analysis was conducted by calculating the productivity levels and catch composition of purse seine operations.The results show that the productivity of purse seine varied across fishing trips, but overall, the gear was considered feasible and relatively efficient. The catch composition was dominated by small pelagic fish, particularly kawakawa (tongkol banyar) at 32% and frigate tuna (tongkol pisang balaki) at 24%, followed by bullet tuna (tongkol pisang cerutu), skipjack (cakalang), mackerel (kembung), and scads (layang deles). These findings indicate that purse seine fishing is well-suited to the characteristics of fish resources in Mamuju waters and has the potential to support sustainable fisheries management.